КРИТЕРІЇ СФОРМОВАНОСТІ ЕКОЛОГІЧНОГО СВІТОГЛЯДУ СТУДЕНТІВ-ЕКОНОМІСТІВ - Душечкіна, Наталія (Збірник наукових праць Уманського державного педагогічного університету, 2020)
В статті розглянуто критерії світогляду особистості різними науковцями. Згідно аналізу даного дослідження, розроблено критерії екологічного світогляду студентів економічних спеціальностей, які представлено такими напрямами: мотиваційно-ціннісним, когнітивно-інтелектуальним, практично-діяльнісним. Доведено і встановлено, що цінності, ціннісні орієнтації, переконання, життєві перспективи є достатньо актуальним завданням для теорії та практики виховання, оскільки від формування екологічного світогляду майбутніх економістів значною мірою залежить екологічний стан нашої країни. В статье рассмотрены критерии мировоззрения личности различными учеными. Согласно анализу данного исследования, разработаны критерии экологического мировоззрения студентов экономических специальностей, представленные следующим направлениям: мотивационно-ценностным, когнитивно-интеллектуальным, практически-деятельностного. Доказано и установлено, что ценности, ценностные ориентации, убеждения, жизненные перспективы достаточно актуальной задачей для теории и практики воспитания, поскольку от формирования экологического мировоззрения будущих экономистов в значительной степени зависит экологическое состояние нашей страны. In the article the different criteria outlook of the individual scientists. According to the analysis of this study the criteria for environmental philosophy students of economic specialties, which are presented following areas: motivational-value, cognitive-intellectual, practical-activity. Proved and found that the values, values, beliefs, life prospects are sufficiently urgent task for the theory and practice of education because of the formation of ecological outlook of future economists largely depends on environmental condition of our country. Values in the structure of environmental philosophy occupy the dominant position and value orientation determine the value and meaning of environmental knowledge and skills in educational and professional activities. Motivational sphere and motivation are understood as the core of the personality, which charged its properties such as orientation, values, attitudes, social expectations, aspirations, emotions and volitional qualities and other social and psychological characteristics. Motivation has a significant impact on the nature of the implementation of ecologically. Formation environmental philosophy made more successful if students developed positive motivation assimilation system of environmental knowledge and skills that are the basis for ecologically indicative of future professional economists. The most important part of environmental philosophy advocates environmental practice or ecological behavior. One of the most powerful means of formation environmental philosophy advocates environmental protection – system of education, which is the implementation of activity-ecological knowledge and skills acquired by students in the educational process.